FATHER-SON RELATIONSHIP IN KHALED HOSSEINI’S THE KITE RUNNER AND CORMAC MCCARTHY’S THE ROAD - Younis, Hala (Humanities Journal of University of Zakho, 2025)
The current paper deals with father-son relationship in the East represented by Khaled Hosseini’s The Kite Runner and in the West which is demonstrated by Cormac McCarthy’s The Road. This study analyzes the characters and explores their relationships with reference to psychological theory of attachment by the renowned British psychiatrist John Bowlby (1907-1990). The two novels reflect biographical accounts of the two authors especially that of Hosseini and his life in Afghanistan and the fatherly figure type he has had like Amir and the majority of the Eastern fathers. Furthermore, it argues that the father and son relationship illustrated by Baba and Amir in The Kite Runner is cold and distant. In contrast, father - son relationship in The Road is an affectionate and loving relationship. This strong bond between the nameless father and son is meant to represent all fathers and the sons especially those in the West since the novel is written about America. The study concludes that all good fathers love their sons whether in the East or West. However, while the father and son relationship in the West in The Road is demonstrated through the father showing his love and taking care of his son. Baba and Amir’s relationship looks distant and cold with a lack of communication on the surface. Nevertheless, the Eastern fathers represented by Baba do love their sons and the sons likewise in hard situations they are willing to work hard and go beyond their abilities to provide for their sons and afford a good education for them.